Effect of Direct Acting Antiviral Drugs on HbA1c in Type 2 Diabetic Patients Infected with Chronic Hepatitis C Infection - Ehsan, Amna; Gull, Wajeeha; Shahid , Arwa; Jamil, Zubia (Indus Journal of Bioscience Research, 2025)
Background: There is emerging evidence that direct acting antiviral therapy in HCV patients affect insulin resistance. This study is being conducted to study the impact of direct acting antiviral drugs on glycaemic control in terms of pre- and post-treatment mean HbA1C among hepatitis C virus positive diabetic patients, treated at tertiary care hospital of northern Pakistan. Material and Methods: This Quasi-Experimental Model study was conducted between 6 Feb 2025 to 31st May 2025 at the Hepatology Department, Fauji Foundation Hospital, Islamabad. A total of 60 male and female diabetic patients with confirmed HCV positive and planned for DAA therapy and having age between 18-75 years were enrolled using the non-probability consecutive sampling after getting aw written informed consent. Baseline HbA1c was determined and patients were followed up monthly. After four weeks of the treatment, the HbA1C and values were repeated. Data was analyzed using SPSS software version 25. Study confounders like were controlled by the stratification. Post stratification, paired t-test was used to see the statically significant difference (p-value ≤ 0.05). Results: The mean age was 51.42 ± 13.35 years, with a predominance of female participants (70%). Paired sample analysis showed that the mean pre-treatment HbA1c was 8.90 ± 2.19%, which significantly decreased to 7.42 ± 1.41% following completion of DAA therapy. The mean reduction in HbA1c was 1.48% (95% CI: 1.20–1.76). This improvement was statistically significant (paired t-test: t = 10.60, df = 59, p < 0.001). A strong positive correlation was observed between pre- and post-treatment HbA1c values (r = 0.91, p < 0.001). Conclusion: The current research proves that a direct-acting antiviral (DAA) treatment of hepatitis C virus (HCV) infection is linked to a meaningful increase in glycaemic control in patients with type 2 diabetes mellitus (T2DM), indicating that the glycated haemoglobin (HbA1c) level declined consistently within all the investigated groups. HCV treatment does not only reduce hepatic complications but also enhances the management of diabetes, which may reduce long-term vascular complications and healthcare expenses, as well.